Evaluation of partial purification and immobilization of lipase from Geotrichum candidum. Issue 3 (July 2015) - Maldonado, Rafael Resende; Aguiar-Oliveira, Elizama; Fogaça, Felipe Massiero; Ramos, Gabriela Giolo; Macedo, Gabriela Alves; Rodrigues, Maria Isabel
Abstract: Partial purification of lipase from Geotrichum candidum was obtained by precipitation using two methods: ethanol (70% v/v) and ammonium sulphate (80% w/v) followed by lyophylization. Recovery factors (RF) from 60% to 140%, concentration factors (CF) from 44 to 66 and lipase activities from 400 to 900 U g − 1 were obtained. Lyophylization is important to maintain the enzymatic activity. In relation to solvent affinity, lyophilized lipase had higher affinity for the polar phase when incubated in phosphate buffer:hexane (1:1) but it had lower stability when incubated in phosphate buffer:ethanol (1:1) at 37 °C. Immobilization onto different supports (alginate beads, niobium–graphite alloy, zeolite and Celite®) revealed the inability of niobium–graphite alloy as a support and good potential for the other supports. Under the circumstances applied, Celite® resulted in an immobilized lipase activity around 90 U g −1 and zeolite presented efficiency around 66%, which indicate to be good alternatives for immobilization of lipase from G.candidum .